DANDING DI PERSIMPANGAN ZAMAN: TRADISI DAN MODERNITAS DALAM KEHIDUPAN REMAJA PEREMPUAN MANGGARAI - Anjelina Jalnisa; Elisabeth Nena; Alfonsius Purnama; Apolonius Puterman; Bernadeta Sia Moi (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Danding dance is a cultural heritage of the Manggarai people's ancestors that functions as a social dance as well as a medium of social expression for adolescents, particularly young women. In an era of rapid globalization and modernization, the existence of Danding faces serious challenges in the form of a shifting interest among the younger generation toward popular culture. This study aims to examine how Danding is positioned in the lives of Manggarai young women amid the tension between tradition and modernity. The method employed is a qualitative approach using observation techniques, in-depth interviews, and documentation studies. The findings reveal that Danding is still regarded as important in terms of cultural identity and as a space for expression among Manggarai women; however, the intensity of young women's involvement has been steadily declining due to the dominance of digital culture and modern lifestyles. Preservation efforts carried out through formal education, cultural festivals, and local arts communities have proven to play a role in sustaining the existence of Danding. This study concludes that an integrative approach between customary values and modern platforms is needed in order for Danding to remain relevant in the lives of contemporary Manggarai young women.